STRATEGI PERANG ELEKTRONIKA DALAM AIR CAMPAIGEN (KAMPANYE UDARA) GUNA MENJAGA KEDAULATAN WILAYAH UDARA NASIONAL - Enggal Leksono; Agus Sudayra; Afrizal Hendra; Muhammad Nakir; Bastari Bastari; IDK Kertawidana; Haposan Simatupang (Sekolah Tinggi Pariwisata Mataram, 2022)
There are still a number of issues that hinder the TNI AU from realizing the development of the TNI AU's Electronic Warfare capability, among others, the organization that organizes trade operations in the TNI AU's operational units is still not ideal, there are still limited software that regulates the implementation of TNI commerce operations, not optimal. preparation of human resources in the field of trading operations, the need for electronic warfare equipment with the latest technology in all operational units of the Indonesian Air Force, and the lack of availability of supporting infrastructure for trading operations. Efforts to anticipate and deal with threats from weapons systems in the current modern war era and maintain national air sovereignty, it is necessary to formulate appropriate strategies, including realizing the development of the Indonesian Air Force electronic warfare organization through the establishment of an organizational structure for the Indonesian Air Force's operational unit and fulfillment of requirements for validation. perrnika organization, realizing the fulfillment of software needs to support the implementation of electronic warfare of the Indonesian Air Force through revision of operational instructions and technical instructions for operational and maintenance of trading equipment, realizing the readiness of personnel carrying out trade operations through the provision of manning personnel according to organizational needs and organizing education and training, realizing the fulfillment of equipment needs equipment to support the TNI AU's commercial operations through the procurement of new equipment, as well as to fulfill the need for supporting infrastructure for the implementation of Electronic Warfare The Indonesian Air Force through the development of infrastructure for a centralized trading database storage facility.